Pengembangan Konseling Realita Dengan Teknik Want, Doing and Direction, Evaluation, dan Planning Untuk Meningkatkan Self Achievement Siswa - Ni Putu Lokita Asmara Dewi; Ni Ketut Suarni; I Ketut Dharsana (Jurnal Bimbingan dan Konseling Indonesia, 2022)
This research is a research and development. This guidebook was created to be used as a reference for Counseling Guidance teachers in carrying out counseling services in schools to improve student self-achievement. The development procedure in this study uses the 4-D modification learning tool proposed by Thiagarajan, namely define, design, development, and disseminate. This study involved the subjects of 5 experts in counseling guidance including 3 lecturers of Counseling Guidance FIP Undiksha and 2 teachers of Counseling Guidance at SMP Negeri 2 Kediri to test the validity of the contents of the product and 10 Counseling Guidance teachers to test the acceptance of the product. To test the effectiveness of the guidebook, researchers involved 7 students as subjects. Of the 22 instrument items used in the assessment by experts, all items of the guidebook have good validity. Based on this assessment, it was found that the content validity index (CVI) of the category guidebook was very appropriate. In the acceptance test of products using PAIT analysis, a mean of 3.79 was obtained which was categorized as B (Good) so that the guidebook was feasible to use. Hypothesis testing shows that the Implementation of the Reality Counseling Theory Guidebook with Want, Doing and Direction, Evaluation, and Planning Techniques is Effective to Improve Student Self Achievement with a count of 2.691 with a significance level of 0.05 and an ES value = 1.016 which means the effect of the guidebook to improve the self-achievement of high-category students. Abstrak: Penelitian ini merupakan penelitian pengembangan. Buku panduan ini dibuat untuk dapat dijadikan acuan bagi guru BK dalam melaksanakan layanan konseling di sekolah untuk meningkatkan self achievement siswa. Prosedur pengembangan dalam penelitian ini menggunakan perangkat pembelajaran modifikasi 4 – D yang dikemukakan oleh Thiagarajan yaitu : (1) Tahap Pendefinisian,(2) Tahap Perancangan, (3) Tahap Pengembangan, (4) Tahap Penyebaran. Penelitian ini melibatkan subjek 5 orang ahli dalam bimbingan konseling diantaranya adalah 3 orang dosen Bimbingan Konseling FIP Undiksha dan 2 orang guru Bimbingan Konseling SMP Negeri 2 Kediri untuk menguji validitas isi produk dan 10 orang guru Bimbingan Konseling untuk menguji keberterimaan produk. Untuk menguji keefektifitasan buku panduan, peneliti melibatkan 7 orang siswa sebagai subjek. Dari 22 butir instrument yang digunakan dalam penilaian oleh pakar/ahli, semua butir buku panduan memiliki validitas yang baik. Berdasarkan penilaian tersebut didapatkan indeks validitas isi buku panduan berkategori sangat sesuai. Pada uji keberterimaan produk yang menggunakan analisis PAIT didapatkan mean sebesar 3,79 yang berkategori B (Baik) sehingga buku panduan layak digunakan. Pengujian hipotesis menunjukkan bahwa Implementasi Buku Panduan Teori Konseling Realita Dengan Teknik Want, Doing and Direction, Evaluation, dan Planning Efektif Untuk Meningkatkan Self Achievement Siswa dengan thitung 2,691 dengan taraf signifikansi 0,05 dan nilai ES= 1,016 yang berarti efek dari buku panduan untuk meningkatkan self achievement siswa berkategori tinggi.